Diagnostic Hystero-Laparoscopy for Evaluation of Female Infertility: A Cross-sectional Study - Maskey, Suvana; Thapa, Jwala; Adhikari, ShreePrasad; Sedhain, Nesuma; Silpakar, Bhawani (Journal of Institute of Medicine Nepal, 2025)
ntroduction Diagnostic hystero-laparoscopy has additional advantage of direct visualization of pelvic pathology along with performing therapeutic surgery at same setting, compared to other diagnostic modalities. This study aims to determine the role of diagnostic hystero-laparoscopy in evaluation of infertile women. Methods This descriptive study was conducted from April to July 2025 including women presenting with infertility and planned for diagnostic hystero-laparoscopy in department of infertility at Paropakar Maternity and Women’s Hospital. Any abnormalities detected during laparoscopy and hysteroscopy were recorded. If any therapeutic procedure was done, that was also noted. A structured proforma was used to collect data and descriptive analysis was done. Results During the study period 36 underwent diagnostic hystero-laparoscopy among which, 20 (55.55%) had primary infertility and 16 (44.44%) had secondary infertility. The mean age was 30.44±4.70 years and the mean duration of infertility was 3.76±3.71 years. The most common pathologies determined on hysteroscopy were uterine polyp and septate uterus, both being 6 in number (16.66%). On laparoscopy tubal block was noted in 22 (61.11%) women followed by pelvic adhesions which was seen in 19 (52.77%) cases. Most frequent therapeutic intervention done during laparoscopy was adhesiolysis (16, 44.44%) and during hysteroscopy were polypectomy and septal resection (6 each, 16.66%). Eleven women (30.55%) had undergone multiple procedures. Conclusion Tubal and peritoneal abnormalities were the two main factors determined on laparoscopy and most prevalent finding on hysteroscopy were uterine polyp and septate uterus. Adhesiolysis, polypectomy and septal resection were the main procedures performed.